Respons Pertumbuhan Bibit Kakao (Theobroma cacao L.) Terhadap Pemberian Kombinasi Tandan Kosong Kelapa Sawit dan Pupuk Nitrogen Pada Media Sub Soil Ultisol - Nasamsir, Nasamsir; Hayata, Hayata -; Akbar, Alvan Zarano (Universitas Batanghari, 2024)
The limited availability of top soil for fertile growing media encourages the alternative to use subsoil which is less fertile but more widely available. The research aims to test top soil substitution using a combination of TKKS and nitrogen fertilizer on the growth of cocoa seedlings (Theobroma cacao L.) in polybags. The research was carried out at Rt. 04, Simpang Rimbo, Alam Barajo, Jambi city and the Basic and Integrated Laboratory of Jambi University, from May to July 2023. The design used is a factorial Completely Randomized Design (CRD), the first factor of the growing media consists of five levels: k1 = top soil + sub soil (2:1), k2 = TKKS compost + sub soil (100 g: 3 kg), k3 = TKKS compost + sub soil (:150 g :3 kg), k4 = TKKS compost + Sub soil (200 g :3 kg), k5= TKKS compost + sub soil (250 g :3 kg). The second factor of N fertilizer dosage consists of three levels: n0 = 0 g urea/plant, n1= 2 g urea/plant, and n2= 4 g urea/plant. Parameters observed included plant height, stem diameter, plant dry weight, root dry weight, amount of chlorophyll in cocoa seedlings aged 21 WAP, media water content, and soil chemical properties. Data were analyzed using analysis of variance, then continued with the DNMRT test at the Î± level of 5%. The results of the research showed that there was a real interaction between the combination of EFB compost and nitrogen fertilizer in the sub-soil planting medium on plant height, seed stem diameter, shoot dry weight, root dry weight and amount of leaf chlorophyll, but the interaction was not significant on the water content of the planting medium. The highest height of cocoa seedlings was found in the k5n2 treatment at 40.43 cm, the largest seed stem diameter was obtained from k5n2 at 13.17 mm, the highest seed crown dry weight was obtained in the k5n2 treatment at 39.97 g, the highest root dry weight was obtained in the k5n2 treatment amounting to 28.37 g, the highest amount of leaf chlorophyll was produced from the k5n1 treatment at 36.90 Î¼mol m-2, and the highest water content of the planting medium was produced from the k5n0 treatment at 41.77%. Based on research conducted, cocoa nurseries can use Ultisol sub-soil planting media treated with a combination of TKKS compost + sub-soil (250 g: 3 kg of soil) and 4 g of nitrogen fertilizer in polybag-1Key words: cocoa, EFB compost, nitrogen fertilizer, Ultisol sub soil